2020
DOI: 10.3390/ijms21062028
|View full text |Cite
|
Sign up to set email alerts
|

Defects in Galactose Metabolism and Glycoconjugate Biosynthesis in a UDP-Glucose Pyrophosphorylase-Deficient Cell Line Are Reversed by Adding Galactose to the Growth Medium

Abstract: UDP-glucose (UDP-Glc) is synthesized by UGP2-encoded UDP-Glc pyrophosphorylase (UGP) and is required for glycoconjugate biosynthesis and galactose metabolism because it is a uridyl donor for galactose-1-P (Gal1P) uridyltransferase. Chinese hamster lung fibroblasts harboring a hypomrphic UGP(G116D) variant display reduced UDP-Glc levels and cannot grow if galactose is the sole carbon source. Here, these cells were cultivated with glucose in either the absence or presence of galactose in order to investigate gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…UDP-glucose and UPD-galactose are utilized in many biosynthetic pathways, including nucleotide and galactose metabolism. However, despite abnormalities in the nucleotide-activated sugars UDP-glucose and UDP-galactose, there were no indications of misdirected N-glycosylation (Figure S4) [27]. In general, metabolome analysis of dried blood spots revealed that PPA1 deficiency can not only lead to the derangement of the galactose metabolism and PPi formation but also broader abnormalities in amino acid, fatty acid and nucleotide metabolism.…”
Section: Discussionmentioning
confidence: 88%
“…UDP-glucose and UPD-galactose are utilized in many biosynthetic pathways, including nucleotide and galactose metabolism. However, despite abnormalities in the nucleotide-activated sugars UDP-glucose and UDP-galactose, there were no indications of misdirected N-glycosylation (Figure S4) [27]. In general, metabolome analysis of dried blood spots revealed that PPA1 deficiency can not only lead to the derangement of the galactose metabolism and PPi formation but also broader abnormalities in amino acid, fatty acid and nucleotide metabolism.…”
Section: Discussionmentioning
confidence: 88%
“…The decrease in l ‐arabitol content reduces the accumulation of cytoprotective substances, resulting in a decrease in the content of synthetic polysaccharides (Zhou et al, 2018). Galactose metabolism provides the precursor uridine diphosphate (UDPG) for polysaccharide synthesis (Durrant et al, 2020). The d‐ mannitol content in the MS group was higher than that in the OS group.…”
Section: Resultsmentioning
confidence: 99%
“…This is a significant advantage over traditional MS methods, which cannot differentiate between isobaric compounds. Using HRMS, the glucose and galactose were reported to have a significant impact on CHO cell metabolism, while other sugars (such as GDP-Fucose, UDP-Glc/UDP-Gal, UDP-GlcNAc/UDP-GalNAc) had no or minor effect ( Durrant et al, 2020 ). HRMS can also be utilized to analyse glycosaminoglycans (GAGs), which are complex carbohydrates that play a critical role in various biological processes ( Torres CL.…”
Section: Evolving Methods and Future Perspectives In Cho Metabolomicsmentioning
confidence: 99%